Recent advances in development of poly (dimethylaminoethyl methacrylate) antimicrobial polymers - Kanth, Shreya; Malgar Puttaiahgowda, Yashoda; Nagaraja, Akshatha; Bukva, Merima (European polymer journal, 2022)
[Display omitted] •Poly (dimethylaminoethyl methacrylate) exhibits bactericidal activity due to its amphiphilic nature.•Polymers can be developed by synthesizing novel monomers, polymers or loading antibiotics to polymer backbone.•A possible mechanism for antimicrobial activity has been discussed.•The use of PDMAEMA polymers can be found in various sectors like biomedical surfaces, food packaging, drug carriers etc. Microbes are omnipresent. They play a prominent role in maintaining the surrounding we live in. Among these microorganisms, pathogenic microbes pose a major threat to public health. During the last century, many medicines with novel solutions to combat microbial infections were discovered. Gradually, the use of these medicine’s/antibiotics started attaining resistance towards these microorganisms. Thus, in recent years, the development of antimicrobial polymers has become the subject of study since they are considered next-generation biocides and provide an environmentally friendly strategy that does not encourage resistance. Polymers have received significant attention in combating bacterial infections, due to their easily modified structure that can be adapted to each microorganism individually. Poly (dimethylaminoethyl methacrylate) (PDMAEMA) is one such polymer that has received lots of attention throughout recent years as it can be tailored accordingly. This review article provides an insight on recent design, synthesis, and development of monomers, homo & copolymers of dimethylaminoethyl methacrylate. And also discusses the detailed mechanisms for exhibiting antimicrobial activity against several pathogenic microorganisms and their applications. This article indubitably serves as a good basis for more advanced approaches in the future for the development of better antimicrobial materials.